PENANDA JAMAK DALAM BAHASA PRANCIS DAN BAHASA INDONESIA - Hayatul Cholsy (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2005)
The pluralities of French can be found in both writing and oral . In writing, there are the additions of -x and -s, or the others variations which depend on the rules of nouns and adjectives . There are the concordances between nouns and adjectives or subjects and predicates in past tense, passive voice, and complete sentence with que . On the other hand, in oral, there are the pronunciations of the articles of nouns and liaison . The pluralities in Indonesian are in repetitions of nouns, verbs, adjectives, the numeral, and the adjectives that have plural meaning .